Facile One-Pot Conversion of (poly)phenols to Diverse (hetero)aryl Compounds by Suzuki Coupling Reaction: A Modified Approach for the Synthesis of Coumarin- and Equol-Based Compounds as Potential Antioxidants - Muthipeedika Nibin Joy; Igor S. Kovalev; Olga V. Shabunina; Sougata Santra; Grigory V. Zyryanov (MDPI AG, 2024)
A series of 16 (hetero)aryl compounds based on coumarin and equol has been efficiently synthesized by exploring the palladium-catalyzed Suzuki cross-coupling reactions. Polyphenol based on coumarin (4-methyl-7-hydroxy coumarin) was initially converted to corresponding coumarin imidazylate and then subjected to Suzuki coupling reaction with 4-methoxyphenylboronic acid to obtain the coupled product. This modified approach was later developed into a one-pot methodology by directly reacting the polyphenol with 1,1-sulfonyldiimidazole (SDI) and boronic acid in situ to obtain the Suzuki coupled product in one step. Moreover, an array of (poly)phenols based on coumarin and equol were later converted to diverse (hetero)aryl compounds by this optimized step-economic protocol. The synthesized compounds were then subjected to the screening of their potential antioxidant activities by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. In our investigation, the compounds 4ah, 4eh, 4gh and 4hh exhibited promising antioxidant potential when compared to the reference standard, butylated hydroxytoluene (BHT). Structure activity relationship (SAR) studies revealed the importance of the presence of electron-donating substituents in enhancing the antioxidant activity of the synthesized compounds.